Search for a new heavy gauge-boson resonance decaying into a lepton and missing transverse momentum in 36 fb - 1 of pp collisions at s = 13 TeV with the ATLAS experiment - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2018)
The results of a search for new heavy W ' bosons decaying to an electron or muon and a neutrino using proton-proton collision data at a centre-of-mass energy of s = 13 TeV are presented. The dataset was collected in 2015 and 2016 by the ATLAS experiment at the Large Hadron Collider and corresponds to an integrated luminosity of 36.1 fb - 1 . As no excess of events above the Standard Model prediction is observed, the results are used to set upper limits on the W ' boson cross-section times branching ratio to an electron or muon and a neutrino as a function of the W ' mass. Assuming a W ' boson with the same couplings as the Standard Model W boson, W ' masses below 5.1 TeV are excluded at the 95% confidence level.